Copyright Regulation for AI-Generated Images Legal Approaches in Indonesia and the United States - Raharja, Made Doni Darma Dananjaya; Sadnyini, Ida Ayu; Angelo, Michael (SASI, 2024)
Introduction: The background of this research addresses the generated image by Artificial Intelligence whether it is protected by copyright, it is based on creating an image is usually created directly by the person, but in this context the image created is made by artificial intelligence.Purposes of the Research: The purpose of this research first to determine the copyright arrangements against images created by artificial intelligence in Indonesia and then to find out related copyright arrangements in the United States related to images generated by artificial intelligence.Methods of the Research: This research uses normative legal research methods, and  the approach used is normative legal research on the basis of the vagueness of norms related to images that degenerate by copyright including copyright. The approach used in this research is a conceptual approach, statutory approach, analytical approach, and comparative approach.Results of the Research: The images generated by AI are protected by copyright, but the subject that is actually protected is the human who commanded the AI to create the image. Where only humans are considered legal subjects that can protect their work. Although AI can create works, AI itself is not considered to have the morality necessary for copyright law protection. Therefore, in the event that an AI creates a work, copyright law protection is extended to the human controlling the AI as the actual creator.